ANALISIS FIKIH WAKAF DAN UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF TERHADAP PEROLEHAN HAK NADZIR PADA PENGELOLAAN WAKAF UANG NADZIR INDIVIDU DIKAMPUNG TAPOS CIKALONG WETAN - Ifa Hanifia Senjiati; Siska Lis Sulistiani; Muhammad Fikri Rais Mubarok (Tahkim (Jurnal Peradaban dan Hukum Islam), 2020)
The development of waqf is now empowered in the form of money asets called waqf money. Money asets can be managed for productive businesses — one of the firms in the field of animal husbandry. However, in Tapos Cikalong Wetan Village, there is control over the results of money waqf management. In which the profit is controlled by nadzir completely. Whereas, based on Constitution No. 41 of 2004 concerning Nadzir's Waqf, it is only entitled to get 10%. The research method used in this study was qualitative with a normative juridical approach. Primary data sources were interviews with wakif and nazhir in Cikalong Wetan Village, and secondary data were journals, books, and other literature. Data analysis was fiqih waqf comparisons, and Constitution Number 41 with in the field then verified then concluding. The result of this study showed that, First, Analysis of Fiqih Waqaf and Constitution Number 41 concerning the obtaining nadzir rights were permitted to take profits in the amount of not more than 10%. Second, the management of money waqf in Tapos Cikalong Wetan Village controlled all the results of productive waqf. Third, Analysis of Fiqih Waqaf and Constitution Number 41, nadzir in Tapos Cikalong Wetan Village had not obeyed the rules that have been determined regarding the wages of nadzir.Keywords: Money Waqf, Nadzir, Constitution.